A 6.5-cm pseudoaneurysm of the superior mesenteric artery managed by primary surgical repair. (February 2013) - Dasari, Bobby V M; Mullan, Michael; Lau, Louis; Loan, William; Lee, Bernard
Superior mesenteric artery (SMA) aneurysms are rare but associated with significant mortality (25–40%) when complicated by rupture or thrombosis. Symptomatic SMA aneurysms, asymptomatic aneurysms of ≥2 cm size and pseudoaneurysms need intervention. We report a case of a 6.5-cm symptomatic SMA aneurysm managed by open surgical repair. At intraoperative exploration, the aneurysm was recognized to be a pseudoaneurysm with a narrow neck (1 mm defect in the native vessel) and was dealt by primary repair. Clinical presentation, the role of radiological investigations and management are discussed. Detailed preoperative assessment of the anatomical characters is essential in planning the intervention for SMA aneurysms. The required information can be obtained by selective interventional angiogram or computed tomographic angiogram with three-dimensional reconstruction. Multi-institutional prospective databases might provide better evidence regarding the timing of intervention, treatment modality, postinterventional follow-up and surveillance of patients with mesenteric aneurysms.